Characterization of pathogen‐inactivated COVID‐19 convalescent plasma and responses in transfused patients. Issue 10 (5th September 2022) - Weisser, Maja; Khanna, Nina; Hedstueck, Anemone; Sutter, Sarah Tschudin; Roesch, Sandra; Stehle, Gregor; Sava, Mihaela; Deigendesch, Nikolaus; Battegay, Manuel; Infanti, Laura; Holbro, Andreas; Bassetti, Stefano; et al.
Abstract: Background: Efficacy of donated COVID‐19 convalescent plasma (dCCP) is uncertain and may depend on antibody titers, neutralizing capacity, timing of administration, and patient characteristics. Study Design and Methods: In a single‐center hypothesis‐generating prospective case–control study with 1:2 matched dCCP recipients to controls according to disease severity at day 1, hospitalized adults with COVID‐19 pneumonia received 2 × 200 ml pathogen‐reduced treated dCCP from 2 different donors. We evaluated severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antibodies in COVID‐19 convalescent plasma donors and recipients using multiple antibody assays including a Coronavirus antigen microarray (COVAM), and binding and neutralizing antibody assays. Outcomes were dCCP characteristics, antibody responses, 28‐day mortality, and dCCP ‐related adverse events in recipients. Results: Eleven of 13 dCCPs (85%) contained neutralizing antibodies (nAb). PRT did not affect dCCP antibody activity. Fifteen CCP recipients and 30 controls (median age 64 and 65 years, respectively) were enrolled. dCCP recipients received 2 dCCPs from 2 different donors after a median of one hospital day and 11 days after symptom onset. One dCCP recipient (6.7%) and 6 controls (20%) died (p = 0.233). We observed no dCCP‐related adverse events. Transfusion of unselected dCCP led to heterogeneous SARS CoV‐2 antibody responses. COVAM clustered dCCPs in 4 distinct groups and showed endogenous immune responses to SARS‐CoV‐2 antigens over 14–21 days post dCCP in all except 4 immunosuppressed recipients. Discussion: PRT did not impact dCCP anti‐virus neutralizing activity. Transfusion of unselected dCCP did not impact survival and had no adverse effects. Variable dCCP antibodies and post‐transfusion antibody responses indicate the need for controlled trials using well‐characterized dCCP with informative assays.